Internet connectivity disruption in Iran (Iran) - Voidly (2026)
CRITICAL severity disruption detected in Iran. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: IR-2026-0666
Keywords: internet disruption; IR; disruption; critical